Redefinisi Kepemimpinan dalam MSDM: Studi Bibliometrik Mendalam tentang Kepemimpinan Transformasional, Kecerdasan Emosional, dan Efektivitas Organisasi - Haetami, Haetami; Purnomo, Yudiyanto Joko; Jasiyah, Rabiyatul; Soegiarto, Ita; Suharmono, Soni (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
HRM leadership has evolved significantly in an era of rapid and complex organizational change. This research uses bibliometrics, focusing on transformational leadership, emotional intelligence, and organizational effectiveness. We found key trends, influential authors, research clusters, and emerging themes. This analysis reaffirms the importance of transformational leadership and emotional intelligence. Works from leading scholars such as Bass, Avolio, Goleman, and Guest remain influential. We also identify emerging leadership paradigms, including agile and inclusive models adapted to modern challenges. Interdisciplinary links with psychology, organizational behavior, and technology management highlight the cross-disciplinary nature of HRM leadership research. Collaborative networks and new scholars enrich perspectives and methodologies. Practical implications emphasize the importance of transformational leadership and emotional intelligence for HRM practitioners, advocating for agile and inclusive models. Future research directions include examining the impact of digital transformation on leadership and the critical role of leadership in promoting diversity and inclusion.